2013
DOI: 10.1016/j.bpj.2012.11.2272
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stability and Substrate Translocation - A Computational Study of the Leucine Transporter

Abstract: a calmodulin regulation site that with many disease mutations reside proximately. using a variety of spectroscopic methods including CD, fluorescence, NMR, we have determined metal binding affinity, stoichiometry, conformational change and binding modes of Ca 2þ and Calmodulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…347 The study showed that the hydrophobic mismatch is different in distinct conformations (outward-open, occluded, inward-open) of LeuT, and that the differences are connected to the structural elements involved in the conformational transitions during the transport cycle. 347,348 Beyond hydrophobic-hydrophilic contacts between the membrane and the embedded protein, specific lipids can regulate the dynamics and conformational transitions of the LeuT-fold NSSs upon direct interactions. Microsecond AA simulations of human dopamine transporter (hDAT) in a PIP 2 -enriched membrane revealed an inward opening of the transporter triggered by PIP 2 -mediated electrostatic association of specific structural motifs.…”
Section: Neurotransmitter Sodiummentioning
confidence: 99%
“…347 The study showed that the hydrophobic mismatch is different in distinct conformations (outward-open, occluded, inward-open) of LeuT, and that the differences are connected to the structural elements involved in the conformational transitions during the transport cycle. 347,348 Beyond hydrophobic-hydrophilic contacts between the membrane and the embedded protein, specific lipids can regulate the dynamics and conformational transitions of the LeuT-fold NSSs upon direct interactions. Microsecond AA simulations of human dopamine transporter (hDAT) in a PIP 2 -enriched membrane revealed an inward opening of the transporter triggered by PIP 2 -mediated electrostatic association of specific structural motifs.…”
Section: Neurotransmitter Sodiummentioning
confidence: 99%